2009
DOI: 10.1590/s1413-86702009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV among blood donors, antenatal women and other patients in a tertiary hospital in Nigeria

Abstract: HIV/AIDS continues to remain a nightmare in the developing nations of the world especially in Nigeria, where about 2.9 million people are living with this problem. This study aimed at determining the sero-prevalence of HIV among both patients and blood donors at the Olabisi Onabanjo University Teaching Hospital, Sagamu, Nigeria. Samples were collected between January 1st, 2005 and December, 31st 2006 and were screened using two rapid test kits, with two different principles (enzymatic and agglutination). Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
1
9
1
Order By: Relevance
“…This is in contrast to some studies done in this country [14][15][16][17][18][19]. It is also in contrast with studies done in other parts of the world with higher prevalence for the infectious agents, in Burkina Faso [20], Cameroun [21], Mali [22], Mozambique [23], Democratic republic of Congo [24,25] and in Tanzania [26].…”
Section: Discussioncontrasting
confidence: 64%
“…This is in contrast to some studies done in this country [14][15][16][17][18][19]. It is also in contrast with studies done in other parts of the world with higher prevalence for the infectious agents, in Burkina Faso [20], Cameroun [21], Mali [22], Mozambique [23], Democratic republic of Congo [24,25] and in Tanzania [26].…”
Section: Discussioncontrasting
confidence: 64%
“…A study in India reported that the mean age of the PPE patients was 34.2±7.5 years [19]. Most of the patients with PPE in this study (68.8%) were less than 45 years old, in keeping with the age group more likely to be HIV infected as reported in similar studies in our environment [20,21].…”
Section: Discussionsupporting
confidence: 84%
“…Full texts of four articles were inaccessible. Twenty-five articles underwent stage 3 screening and 23 articles were selected29–51 after excluding two studies that did not provide the details of HIV diagnostic tools (figure 2).…”
Section: Resultsmentioning
confidence: 99%